Revolution! Svenska erfarenheter från Ryssland - Birgitte Beck Pristed (Nordisk Østforum, 2019)
Abstract: Review of Revolution! Swedish experiences from Russia Birgitte Beck Pristed reviews Revolution! Swedish experiences from Russia, edited by Alexander Husebye, with contributions by Bengt JAngfeldt, Ulrika Knutson, Martin Kragh, Benito Peix Geldart, Gunnar Åselius. The volume is issued by the Swedish Center for Business History on the occasion of the 100th anniversary of the Russian Revolution and examines the postrevolutionary fate of Swedish entrepreneurs and their extensive business activities in Russia.